Evaluating the Impact of Celebrity Endorsers and Country of Origin on Consumer Purchase Decisions - Fauziridwan, Meydy (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to evaluate the impact of Country of Origin (COO) and celebrity endorsement on consumer purchase decisions, focusing on Innisfree skincare products among students at Universitas Muhammadiyah Purwokerto. A quantitative research approach using Structural Equation Modeling (SEM) was employed, with data collected from 294 respondents. The findings reveal that COO significantly influences purchase decisions, where the perception of the country of origin, particularly South Korea, enhances consumer trust and perceived product quality. On the other hand, celebrity endorsement was found to have no significant impact on purchase decisions, although there is potential for improvement with better alignment between the celebrity and the brand. The interaction between COO and celebrity endorsement strengthens brand perception, particularly among young consumers who are influenced by digital media. This study provides insights into the importance of COO in marketing strategies for skincare products, while celebrity endorsement serves as an additional factor that can increase brand attractiveness.